APLIKASI MOBILE LAYANAN ADMINISTRASI DESA/KELURUHAN UNTUK LAYANAN DI ERA PANDEMI COVID 19 - Yaman Khaeruzzaman; Adhi Kusnadi; Marlinda Vasty Overbeek; Moeljono Widjaja; Dennis Gunawan; Ni Made Satvika Iswari (Politeknik Negeri Sriwijaya, 2022)
Administrative services are a routine activity carried out by village and/or sub-district offices andallow for mobility and crowding of residents which should be avoided during the current pandemic.The administrative service procedure requires a series of approvals from the head of the RT, headof the RW, the apparatus and the head of the village/kelurahan so it takes time. Administrativeservices will be very good if they can be carried out electronically using devices that are commonlyowned by citizens such as smart cell phones so that they can be carried out faster, complying withrecommendations to avoid mobility and crowds and the slogan